Analysis of Transparency, Accountability, and Corporate Governance on Financial Performance in Digital Companies - Octojaya Abriyoso; Dodi Siswanto; Samsidar; Rihfenti Ernayani; Musran Munizu (Indonesian Journal of Business Analytics, 2026)
The development of financial performance in the digital company sector over the past decade reflects a highly dynamic transformation from an aggressive growth phase to a more stable profitability phase. In the early stages of growth, digital companies tended to prioritize market expansion and massive user acquisition, often recording negative operating cash flow in order to build a dominant ecosystem. The purpose of this study is to analyze the influence of transparency, accountability, and corporate governance on financial performance in digital companies. This research is a comparative causal study with a quantitative approach. The population of this study was digital companies listed on the Indonesia Stock Exchange during the reporting years 2020 to 2025, with criteria including technology issuers, data centers, and digital banks. The sampling technique used was purposive sampling. Based on predetermined criteria, the sample in this study was 15 digital companies. This research analysis uses multiple linear regression analysis. The results show that transparency has a significant effect on financial performance in digital companies. Accountability has a significant effect on financial performance in digital companies. Corporate governance has a significant effect on financial performance in digital companies.